Les Temps d’Activités Périscolaires (TAP) : expérience scolaire et compétences transversales développées par les élèves - Gaelle Espinosa; Véronique Barthélemy; Benoit Dejaiffe (Éducation et Socialisation)
This article aims at showing which transversal skills are developed by pupils during extracurricular activities (TAP). According to a comprehensive paradigm, a qualitative and quantitative survey was led to primary school pupils in Meuse. This article studies three transversal skills: cognitive, social and socio-affective ones. In other words, are the pupils able to understand the new school organization (including their activity choices and strategies)? Might the TAP influence pupils’ sociability and socialization as well as adult relationship? Our results show that the TAP lead to new organizational features and relationships influencing pupils’ behaviors in the classroom or at school. Pupils learn transversal skills in the classroom and at school, reinforcing their school experience.